Biofloc technology: principles focused on potential species and the case study of Chilean river shrimp Cryphiops caementarius - David Antonio Ulloa Walker; María Cristina Morales Suazo; Maurício Gustavo Coelho Emerenciano (Reviews in Aquaculture, 2020)
The accelerated growth of aquaculture has caused environmental impacts in many countries. Examples include the use of large volumes of water, discharge of effluents with high nutrient content, the occupation of large areas, natural habitat alternation and the escape of exotic species. Biofloc technology (BFT) is an aquaculture tool that requires minimal water exchange, promotes the nutrient recycling optimizing resources and produces natural food in situ by forming suspended microbial aggregates in the water (bioflocs). These microorganisms provide multiple benefits such as water quality control, pathogen resistance and nutritional supplementation. Species such as Litopenaeus vannamei and tilapia have been successfully applied in BFT. In addition, there are also an increasing number of studies focused on alternative species with promising results. This paper describes essential aspects of biofloc technology, its application in aquaculture and the potential to extend its benefits to new aquaculture species such as Chilean river shrimp Cryphiops caementarius . This paper describes the future challenges of this technology as well as opportunities for its application.